A könnyen érthető kommunikáció (KÉK) használatának lehetőségei a MID-oktatásban (Selkokielisen kommunikaation käytön mahdollisuuksista unkari vieraana kielenä -opetuksessa) - Varga, Judit (Külgazdasági és Külügyminisztérium, 2025)
The paper gives an overview of easy-to-understand communication and presents its application opportunities in teaching Hungarian as a foreign language. After discussing the terminological issues, the paper summarizes the history of easy-to-understand communication, explains its location in the communication field and presents the results of research on the measurability of the complexity of easy-to-understand texts. After reviewing the recommendations on lexical, morphosyntactic and textological characteristics compiled by international organisations, it gives an overview of the grammatical and textological characteristics of easily understood texts. It parallels the terms Easy Language (EL) and Plain Language (PL) used in English literature to determine their usability in teaching Hungarian as a foreign language. Finally, the paper makes recommendations for the use of easy-to understand texts in teaching of Hungarian as a foreign language. Keywords: Easy Language (EL), Plain Language (PL), easy-to-understand text Kulcsszavak: könnyen érthető nyelv, közérthető nyelv, könnyen érthető szöveg